Assessing the Governance of Ecotourism in a Forest-Protected Areausing Social Network Analysis: Sungei Moroli, Kampung Luanti Baru, Kawang Forest Reserve, Sabah. - Nor Aziah Abd Kadir; Mohd Iqbal Mohd Noor; Amirah Azzeri; Mohd Hafiz Jaafar; Muhammad Fuad Abdullah (UiTM, 2024)
Bioresources and Environment Volume 1 No.1 Page (50-65)